THE IMPACT OF THE "PEKAN GAWAI DAYAK" CULTURAL EVENT ON TOURISTS' DECISION TO VISIT PONTIANAK CITY - Natasha, Cindy; Facrureza , Dewanta (Moestopo International Review on Social, Humanities, and Sciences, 2024)
This study aims to determine the impact of the "Pekan Gawai Dayak" cultural event on tourists' decision to visit Pontianak City. The research uses a quantitative approach with a causal relationship type of study. The subjects of this research are limited to tourists who attended the 37th Pekan Gawai Dayak Pontianak event in 2023. Data collection techniques include the use of questionnaires. Data analysis techniques use correlation tests with the help of SPSS software version 25. Based on the research results, several conclusions can be drawn, First, the Spectacularisation dimension has a significant partial influence on the Decision to Visit, as indicated by a t-value of 2.335 > t-table (1.98) and a significance value of 0.022 < 0.05. Second, the Theme dimension does not have a significant partial influence on the Decision to Visit, as indicated by a t-value of 1.276 < t-table (1.98) and a significance value of 0.205 > 0.05. This means that respondents did not consider the theme of the Pekan Gawai Dayak event when deciding to attend the event. Third, the Immersion and Participation dimension has a significant partial influence on the Decision to Visit, as indicated by a t-value of 2.324 > t-table (1.98) and a significance value of 0.022 < 0.05. Fourth, the "Pekan Gawai Dayak" cultural event has a positive and significant simultaneous influence on tourists' Decision to Visit Pontianak City, as indicated by an F-value of 10.809 > F-table (2.70) and a significance value of 0.000 < 0.05. Furthermore, the coefficient of determination indicates that the cultural event influences 53.6% of tourists' decision to visit Pontianak City, while the remaining 46.4% is influenced by other factors not examined in this study.